Sign control chart based on ranked set sampling. Issue 5 (3rd September 2018) - Asghari, Samaneh; Sadeghpour Gildeh, Bahram; Ahmadi, Jafar; Mohtashami Borzadaran, Golamreza
ABSTRACT: In this paper, ranked set sampling is proposed for constructing a non-parametric quality control chart based on sign statistic for monitoring the process center when the units are difficult and costly to measure. The characteristics of run length such as average, median and standard deviation are used as criteria to compare two sampling schemes: ranked set sampling and simple random sampling. Cauchy, double exponential and normal distributions are applied to investigate the performance of sign control chart based on studied sampling schemes. The proposed control chart is illustrated with a real data set. The results indicate that when the process starts to get out of control, the chart based on ranked set sampling reduces the run length characteristics values.